An Overview of Laser Surface Modification of Die Steels - S. N., Aqida (2008)
In recent years, surface modification using advanced heat source like laser has been replacing the conventional methods to produce amorphous microstructure via rapid solidification. Due to the benefits of laser to enhance the tribological and mechanical properties of materials’ surface, several laser surface processing were developed including laser surface modification, namely laser alloying, transformation hardening, surface amorphization, shock hardening and glazing. In high temperature applications, the laser surface modification technique is beneficial to prolong the die life cycle, and also to improve the surface roughness of thermal barrier coatings (TBC). To produce the amorphous layer at a particular depth, laser parameter such as irradiance, frequency, and exposure time are controlled. Variations of parameter may result in modified microhardness properties of heat affected zone and transition zone. Nevertheless, works on laser glazing of bearings, railroad rails and TBC had proven the surface properties were enhanced through laser glazing to cope with excessive load, wear, fatigue, bending and friction demand.